Socio-economic composition of low-acuity paediatric presentation at a regional hospital emergency department - Alele F; Callander E; Emeto T; Mills JE; Watt K (Wiley)
Aim Despite increasing rates of emergency department (ED) utilisation, little is known about low‐acuity presentations in children ≤5 years. The aims of the study were to estimate the proportion and cost of low‐acuity presentations in children ≤5 years presenting to the ED and to determine the relative effect of socio‐economic status (SES) on paediatric low‐acuity presentations at the ED. Methods This is a retrospective observational study of children ≤5 years presenting to the Cairns Hospital ED over 4 years. A multivariate logistic regression model was used to assess the association between SES and low‐acuity presentations. Cost of low‐acuity presentations was calculated based on triage score and admission status, using costs obtained from the National Hospital Cost Data Collection. Results A total of 23 086 children were included in the study, of whom 56.7% were male (mean age = 1.85 ± 1.63 years). Approximately one‐third of ED visits were low‐acuity presentations (32.4%), and low‐acuity presentations increased progressively with SES. In multivariate analysis, children from families with very high SES were twice as likely to have a low‐acuity presentation (odds ratio 2.17; 95% confidence interval, 1.66–2.85). Low‐acuity ED presentations cost the health‐care system in excess of A$895 000–A$1 110 000 per year. Conclusions These findings demonstrate that a significant proportion of paediatric ED visits are of low acuity and that these visits yield a substantial cost to the health system. Further research is required regarding care givers' rationale and potentially other reasons underlying these low‐acuity ED presentations.
"This is the pre-peer reviewed version of the following article: Alele, F. O., Callander, E. J., Emeto, T. I., Mills, J. and Watt, K. (2018), Socio‐economic composition of low‐acuity paediatric presentation at a regional hospital emergency department. J Paediatr Child Health, 54: 1341-1347. doi:10.1111/jpc.14079, which has been published in final form at http://dx.doi.org/10.1111/jpc.14079 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions."
Keywords: child, pre-school; emergency services, hospital; infant; infant, newborn; social class; Child, Preschool; Cross-Sectional Studies; Emergency Service, Hospital; Female; Health Care Costs; Health Services Misuse; Humans; Infant; Logistic Models; Male; Patient Acuity; Retrospective Studies; Socioeconomic Factors; Triage; 1103 Clinical Sciences; 1114 Paediatrics and Reproductive Medicine; 1117 Public Health and Health Services